Living (Ek)statically: Educating-within-place and the Ecological Imagination - Kentel, Jeanne Adele; Karrow, Douglas (Journal of the Canadian Association for Curriculum Studies, 2010)
This paper explores the concept of educating-within-place, existentially derived through a series of immediate and direct experiences within several old growth forests in southern Ontario, and how this might inform notions of the ecological imagination. Our ruminations are guided by several ongoing research endeavours, some existential, others empirical. We take pause in order to examine what we have been doing in the field of Canadian curriculum studies whilst grasping towards a broadened perspective of teacher educating. To theoretically frame this pursuit we draw upon the notion of Ekstasis in order to engage in a pedagogy that considers possibilities through the senses and sensibilities of teacher candidates. In doing so we examine ways of being that move beyond the technocratic and cultivate a living curriculum.